2014
DOI: 10.1109/tie.2013.2282605
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Transformer Faults Using Frequency-Response Traces in the Low-Frequency Bandwidth

Abstract: This paper describes a new procedure which facilitates the frequency response curve interpretation in the low frequency bandwidth. The procedure is able to estimate the magnetization inductance and winding capacitance, for each transformer phase by only using data from its frequency response. The described calculation procedure uses an R-L-C electrical equivalent circuit developed to simulate the impedance measured in the frequency response test. The procedure takes into account the magnetic coupling among dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, the simulation and experimental test have been performed without considering a magnetic core owing to the fact that within a high-frequency range (usually higher than 10 KHz), inductance changes due to increased eddy current in the core. Indeed, the magnetic field originated from eddy current prevents the penetration of magnetic flux into the core [31]. Therefore, within a high-frequency range, the magnetic core can be overlooked.…”
Section: Table 2 the Capacitance Between The Hv And LV Disks (Pf)mentioning
confidence: 99%
“…Furthermore, the simulation and experimental test have been performed without considering a magnetic core owing to the fact that within a high-frequency range (usually higher than 10 KHz), inductance changes due to increased eddy current in the core. Indeed, the magnetic field originated from eddy current prevents the penetration of magnetic flux into the core [31]. Therefore, within a high-frequency range, the magnetic core can be overlooked.…”
Section: Table 2 the Capacitance Between The Hv And LV Disks (Pf)mentioning
confidence: 99%
“…After the internal short circuit happens, electromagnetic force would cause winding deformation and frequency response analysis (FRA) is very sensitive to this [6]. Accuracy and application of FRA method have been extensively discussed in [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, there are proposals suggesting the use of models to perform the diagnosis [10][11][12][13]. However, experience has shown that the different frequency bandwidths of the SFRA trace are related to different elements within the transformer, in the lowfrequency bandwidth greatly influences the magnetic core [14].…”
Section: Introductionmentioning
confidence: 99%